A robotic system to prepare IV solutions. (November 2018) - Unluturk, Mehmet S.; Tamer, Ozgur; Utku, Semih
Highlights: An oncology drug preparation system with a communication server accepting oncology prescription orders have been developed. This developed system achieves the time and the gravimetric control of oncology medicines administered through vascular route. Ensuring that preparation of the correct dosage. Ensuring the registration of administration electronically. Abstract: Drugs need to be used regularly and correctly in order to be effective. When medicines are used correctly, negativities that threaten human health and life can be avoided, but they can cause unwanted situations that can occur until the end of life when they are used incorrectly. The most common drug administration errors in hospitals are: The wrong dosage of the drug given to the patient, the timing and / or the method of administration, the wrong drug given to the patient, the drug given to the wrong patient, or even not given. Furthermore, the information about the drug that is administered to the patient may not be registered at all. In this research, a robotic drug preparation system and a communication server accepting prescription orders have been developed. Component engineering methodology is further utilized in the design of the Drug Preparation System to maximize reuse, increase product reliability, reduce design, code and test efforts. The IV Robotic Drug Preparation Robot is composed of a robotic work station and a Cartesian carrier to carry the work station to the desired location. The robotic work station has several grippers to handle syringes, to pull the piston of the syringe and to lock the closed system connector to the vial. The IV Robotic Drug Preparation System and communication server are developed and being used in the hospitals. Due to this system, medicines left unused in vials can be used and a great amount of savings is obtained from the drug purchases.